(untitled) (Research, Society and Development, 2021)
A problem in relation to medicine concentration is linked to difference of age of the patients when the medicine was formulated for a pattern age, for instance, for adults. The use of this kind of medicine for children must be calculate correctly and some formulas based in the empirical mathematical methods were suggested and they are used nowadays; however, patients form a same pattern age but with different weight shows a different biotype and requires a different concentration of medicines, as well as the children and the elderly people. According, in this work, based on the mechanical mathematical model using the relation area/volume, a more exact calculus including the metabolism, was proposed to generate a more accuracy formula to calculate the medicine concentration for children and for people of different weight.